The Effectiveness of Lavender Aromatherapy in Improving Sleep Quality in Hemodialysis Patients : A Literature Review - Liana Veranika; Nurina Aulia Hanun; Fahrun Nur Rosyid; Puji Kristini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Chronic Kidney Disease (CKD) is a condition caused by structural or functional abnormalities characterized by a decrease in the glomerular filtration rate (GFR). One of the treatments for CKD patients is hemodialysis (HD). Sleep disorders are among the complications of hemodialysis. Administering lavender aromatherapy is a method to improve the sleep quality of patients. This study uses a literature review method. Articles were searched on ScienceDirect, PubMed, and Google Scholar using advanced search with the keywords